Animate some novel erasure codes from a web demo - Le, Quang Hoa (2014)
Final Year Project – FYP is the last main project I need to complete as a requirement of Bachelor of Computer Science in Nanyang Technological University. My FYP is mainly focus on novel erasure code which includes concepts of abstract algebra and finite field. The main technique I have use in this project is Local Reconstruction Code – LRC and Galois Field for encoding and decoding stored data. For web – demo animation, I have use ASP.NET MVC 4 as the framework. My program allows user to input data in type of bits and demo how data is encoded and decoded by LRC. As this project is about animation and demo, the user input is assume to be bare bits, LRC is supported to have small number of fragments and the Galois Field is only about GF(2n).